Tempo of route overcoming in sport climbing - Kotchenko, J. V. (The Russian Journal of Physical Education and Sport, 2017)
Annotation. The article gives the results of one of the most important factors study, which influences the effectiveness of competition - tempo of competitive route overcoming. Materials. The regularities of tempo characteristics are considered during the performances of women at International competitions in climbing. The aim of the research is the search for the ways of competitive effectiveness increase. The results are based on the results of 1600 starts analysis among female athletes at 38 stages of the World Cup and 3 World championships. Research methods: literature analysis, description, modeling, methods of mathematical-statistical analysis. Results. It was revealed that most female athletes manage to keep high tempo indices within 6-8 seconds for one effective movement only during the first 2-3 minutes of the performance. Evident tempo activity decrease is seen, approximately, during the 5th minute of a clear time of climbing and during the route overcoming with the tempo more than 10 seconds it is almost impossible to achieve good results. During the analysis separate cases were determined, when female athletes of high qualification kept very high tempo of moving (approximately 6 seconds) during a long-term period (till 400 seconds). Comparative analysis of qualification and semifinal-final stages showed, that at more difficult routs there is the increase of tempo indices to 9,1%. Quickness of making decisions and the speed of the separate motional actions fulfillment decrease happens in terms of high physical expenditures and a high level of focusing. In such kind of conditions only leaders can keep a high tempo of climbing, especially at long distances, when maximum final results are more than 40 points. The research works helped to reveal, that a female athlete`s tempo of movement at a competitive route is in converse nonlinear connection with the final result, the degree of connection R = 0,26. On the basis of the received regularities a regressive model of tempo interconnection with the result of the performance is created. The model helps to make approximate calculation of a female athlete`s time movement schedule along the route. Most of effective indices are situated in the part of low (according to the module) value of tempo: from 6 to 9 seconds and such kind of regularity is prospective enough from the point of view of its practical realization in competitive process. Conclusion. Contribution of tempo into the final result, in case of correct tactics of movement, can be 7,3%. Regressive analysis showed, that tempo characteristic of movement, which is close to the upper bound of the set values of the contribution into the result and partial correlation, can have a considerable positive influence on general result of sports performance.